Aptamer-based environmental biosensors for small molecule contaminants. (June 2017) - Nguyen, Van-Thuan; Kwon, Young Seop; Gu, Man Bock
Graphical abstract: Highlights: The EIS aptasensors may overcome the issues related to the molecular weight of the targets. The integration of nanomaterials may enhance the functions of the aptasensors greatly. The modification of aptamer sequences may have great potential in dealing with small molecular targets. Abstract : Aptasensors are promising biosensors, which take advantage of using aptamers as a recognition element. The combination of the excellent characteristics of aptamers and the leading detection platform techniques, such as optical, electrochemical with nanomaterial-integrated, or mass-sensitive techniques with high sensitivity and specificity draws a promising view for the application of the aptasensors for the detection of harmful small toxic chemicals and real-time monitoring in the environments. In spite of attraction of aptasensors, application of them is limited to the complex environment due to the facts that how the immobilization of aptamers onto the surface affects the functions of aptamers and their structures for the detection of environmental contaminants are not clearly known. This review examines the most recent update on the selection of aptamers for small molecules, the development and application of aptasensors in the detection of small molecule contaminants in environment. Additionally, their applications to the real samples as environmental monitoring reported in the publications also are reviewed.